High-resolution TOF with RPCs - Fonte, P. (2002)
In this work, we describe some recent results concerning the application of Resistive Plate Chambers operated in avalanche mode at atmospheric pressure for high-resolution time-of-flight measurements. A combination of multiple, mechanically accurate, thin gas gaps and state-of-the-art electronics yielded an overall (detector plus electronics) timing accuracy better than 50 ps [sigma] with a detection efficiency up to 99% for MIPs. Single gap chambers were also tested in order to clarify experimentally several aspects of the mode of operation of these detectors. These results open perspectives of affordable and reliable high granularity large area TOF detectors, with an efficiency and time resolution comparable to the existing scintillator-based TOF technology but with a significantly, up to an order of magnitude, lower price per channel.